Non-invasive diagnosis of chronic beryllium disease in workers exposed to hazardous dust in Israel. Issue 9 (2nd December 2009) - Fireman, E; Mazor, O; Kramer, M; Priel, I; Lerman, Y
Abstract : Objectives: Chronic beryllium disease (CBD) is caused by prolonged occupational exposure to beryllium and is characterised by various clinical presentations, mostly pulmonary. The inflammatory process involves non-caseous granulomas and proliferation of CD4+ cells. CBD is diagnosed by lung biopsy showing tissue granuloma formation, and by the beryllium lymphocyte proliferation test (BeLPT) for past exposure and sensitisation to beryllium. The induced sputum (IS) technique was developed for diagnosing asthma, chronic obstructive pulmonary disease and interstitial lung diseases. A CD4/CD8 ratio >2.5 in T cells from IS is a positive result for granulomatous lung diseases. We previously revealed that dental technicians are exposed to excessive levels of beryllium. The efficacy of IS (CD4/CD8 >2.5) and BeLPT in diagnosing CBD in 17 workplaces where beryllium was present was evaluated. Methods: All consecutive patients with a clinical suspicion of CBD referred to our institution for diagnosis and management were enrolled. Results of the gold standard lung biopsy with BeLPT were compared to the non-invasive IS+BeLPT. Kappa and McNemar tests evaluated agreement levels. Correlations between demographic and clinical parameters and a confirmed diagnosis of CBD were analysed. Results: The two approaches were compared in 57 of 98 subjects. There was a high level of agreement (κ 0.920) between IS+BeLPT and biopsy+BeLPT. IS+BeLPT had a specificity of 97.3% and sensitivity of 87.5%. 21 of 87 exposed workers (24%) had CBD, of whom 12 were dental technicians (p=0.044 dental technicians versus all other occupations). Conclusions: This study demonstrated that the CD4/CD8 ratio in IS together with positive/negative BeLPT findings can be used in diagnosing CBD.